Complex and Innovative Virtual Learning Environments: An Experience of Participatory Creation from an Emergent Paradigm - Morado, María Florencia (2018)
This paper starts with a participatory action research process, which aims to analyze the guidelines of the emerging paradigm and propose an alternative for building virtual learning environments (VLE) epistemologically consistent with this paradigm. Building virtual learning environments is presented as a challenge for teachers, especially for those who epistemologically adhere to the concepts of the emerging paradigm. Teachers find that the tools available encroach on their pedagogical and creative abilities. Two workshops were held with seven people who completed the research and the building process of their environments. In conjunction with the teaching staff, in the process were defined the guidelines of the emerging paradigm that were necessary to recover to build VLE; the teachers explored tools within the Moodle platform and others from Internet. Then, they co-constructed their environments in a recursive process of analysis and production.